The Relationship of Knowledge Levels Among Clean and Healthy Life Behaviour With The Use of Latrine - Widia Astuti; Fitria Hari Wibawati; Rani Devayanti (Wijaya Husada, 2020)
Clean and healthy lifestyle program is a social engineering that aims to make community membersas agents of change in order to improve the quality of everyday behavior with the goal of clean andhealthy living. The layout of this program involves several elements that are a place of activity ineveryday life. Usage of healthy toilets is one indicator of the clean and healthy lifestyle program whichplays a very important role in improving public health status. This study aims to determine how theknowledge level about clean and healthy lifestyle program affects the use of healthy toilets at MekarWangi Health Center working area, Bogor in 2019.The population in this study is the community at Mekar Wangi Village in Mekar Wangi HealthCenter Working area, Bogor. This research used cross sectional design. The total sample in this studywas 117 respondents, taken by accidental sampling technique. Data analysis used univariate andbivariate analysis using Kendall Tau Correlation.The results showed 88 (75.2%) of respondents were knowledgeable about clean and healthylifestyle program, whereas 29 (24.8%) of respondents were less knowledgeable about the program. Onthe other hand, 62 (53%) of respondents used healthy toilets, while 55 (47%) of respondents did not usehealthy toilets. Based on the results, the p value obtained was 0.000 with significant value <0.05.The results showed there was a correlation between the knowledge level about clean and healthylifestyle program with the use of healthy toilets at the working area of Mekar Wangi Health Center,Bogor in 2019. The results of this study are expected to be a form of input for Mekar Wangi Bogor CityHealth Center to further increase efforts in addressing health behavior and continue to give attentiontowards the community’s knowledge in their work area.